المسـاهمـة في دراسـة العـلاقـة الفيتـوكيميـائيـة والفيـزيـولـوجيـة التطفليـة بيـن نبـات الذنـون Cistanche violacea (Desf.) Beck. الطفيـلي والنبـاتات المضيفـة لـه الزيتـة Dur. Limoniastrum guyonianum والبـاقـل Haloxylon articulatum Bioss - علية, فاطمة (Universty of Eloued جامعة الشهيد حمة الأخضر, 2022)
الملخص: بغية المساهمة في فهم مدى تأثير العلاقة التطفلية على كل من النبات الطفيلي والنبات العائل، قمنا بهذا العمل الذي يهدف إلى دراسة العلاقة الفيتوكيميائية والفيزيولوجية التطفلية بين نبات الذنون Cistanche violacea (Desf.) Beck. الطفيلي وعائليه كل من: الزيتة Limoniastrum guyonianum Dur. والباقل Haloxylon articulatum Bioss. الناميين بمنطقة وادي سوف. وللقيام بهذه الدراسة تم قطف كل طفيل بالتوازي مع عائله من حيث المكان والزمان، فقطف نبات الباقل خلال مرحلة نموه الخضري والذنون المتطفل عليه خلال مرحلة نموه الثمري من منطقة الخمسين التابعة لبلدية الرقيبة، في حين قطف نبات الزيتة خلال مرحلة نموه الزهري والذنون المتطفل عليه خلال مرحلة نموه الثمري من منطقة سبيطار الذيب التابعة لبلدية المقرن. وبعد تجفيف وطحن العينات أجريت عليها جملة من الاختبارات والفحوصات الفيزيوكيميائية والفيتوكيميائية. فمن الجانب الفيزيوكيميائي بلغت نسبة الحموضة والناقلية الكهربائية في الذنون المتطفل على الزيتة 5.63±0.03، 7.05±0.05 mS/cm، بالترتيب، بينما قُدرتا في نظيره المتطفل على الباقل بـ 5.35±0.08 و5.27±0.06 mS/cm، على التوالي، أما عن قيم المادة المعدنية والمادة العضوية فقد تناسبتا عكسيا عند العينات الأربعة المدروسة. في حين سجلنا أعلى القيم الكمية للكربوهيدرات والدهون في نبات الذنون المتطفل على الزيتة 43.832±0.056 mg/g DM؛ 12.398±0.024 mg/mL، على التوالي، بينما كانت أفضل القيم الكمية للمحتوى البروتيني في نبات الذنون المتطفل على الباقل (15.1±0.071 mg/g DM). أما من الناحية الفيتوكيميائية أسفرت نتائج الكشف الكيميائي على اِحتواء النبات الطفيلي بإختلاف عائله على كل من: الفلافونويدات، التانينات، الأنثوسيانينين، الستيرولات والتربينات الثلاثية، كما اتفقا في غياب كل من: الصابونوزيدات والقلويدات؛ بالإضافة إلى هذا، قمنا بتحضير كل من المستخلص: الخام، الفلافونويدي طور أسيتات الإيثيل، العفصي والأنثوسيانين، حيث سجلنا أعلى مردود عند المستخلص الخام للذنون المتطفل على الباقل (16.183 %)؛ كما قمنا بتقدير المحتوى الكمي لكل من: عديدات الفينول الكلية، الفلافونويدات، التانينات والأنثوسيانينين من المستخلصات الخامة، وسجلنا لدى مستخلص الذنون المتطفل على الزيتة قيم أقل من نظيره المتطفل على الباقل والتي كانت: 19.055±0.197 mg E GA/g Ex؛ 5.769±0.353 mg E Q/g Ex؛ 0.121±0.002 mg E GA/g Ex و0.167±0.047 mg E C-3-G/g Ex على التوالي. أما عن التقدير النوعي باستعمال الـ HPLC، فقد أسفرت النتائج عن وجود تقارب في العدد الكلي للمركبات الفينولية لكلا الطفيليين بينما سجل عدد أكبر من المركبات عند العائليين، حيث سجلنا في مستخلص الذنون المتطفل على الباقل سبع مركبات مرجعية من أصل 57 مركبا والتي تمثلت في كل من: Gallic acid; Chlorogenic acid; Vanilin; p-Coumaric acid; Rutin; Naringin; Quercetin. في حين دلّ التحليل الطيفي باستعمال الأشعة تحت الحمراء (FTIR) للمستخلصات النباتية على وجود كل من الوظيفة الهيدروكسيلية (OH)، مجاميع الميثيل (CH)، بالإضافة إلى مجاميع الكربونيل (C=C / C=O)؛ إلى جانب الروابط المميزة للحلقات العطرية (C-C). أما النشاطية المضادة للأكسدة فقد أسفرت عن تميز المستخلص الفلافونويدي لنبات الذنون المتطفل على الزيتة بأفضل كفاءة كاسحة للجذر الحر IC50= 0.011±0.002 mg/mL) DPPH•). في حين أبدى المستخلص العفصي لكلا الطفيليين أحسن كفاءة لإرجاع شوارد الحديد والقدرة الكلية المضادة للأكسدة حيث سجلنا لدى مستخلص نبات الذنون المتطفل على الزيتة القيم EC50= 0.055±0.001 mg/mL و488.493±0.060 g E As A/g Ex، بينما أبدى المستخلص العفصي لنبات الذنون المتطفل على الزيتة أفضل معامل واقي من الأشعة فوق البنفسجية والذي قُدر بـSPF = 27.434±0.020. إحصائيا تبين أن لاختلاف النبات العائل فروقات ذات دلالة معنوية على الخصائص الفيزيوكيمييائية والفيتوكيميائية للنبات الطفيلي؛ حيث تجلت هذه التأثيرات بوضوح من خلال الفروقات الملاحظة بين المحتوى الكمي الكلي للمادة العضوية والمحتوى الكمي لمستقلبات الأيض الأولي، وكذا الفروقات بين المحتوى الكمي لعديدات الفينول وأجزاؤها، إلى جانب الاختلاف المدوّن بين مختلف المستخلصات المدروسة وقيم نشاطيتها المضادة للأكسدة. عموما ومن خلال النتائج المسجلة يمكن القول إن لإختلاف النبات المضيف في العلاقة التطفلية تأثيرا كميا ونوعيا على المحتوى الأيضي للنبات الطفيلي، وأن هذا التأثير ينعكس مباشرة على فاعلية مواده الفعالة، كما إن هذه العلاقة الحيوية من شأنها أن تأثر سلبا على الأداء الكيموحيوي للنباتات المضيفة؛ وأن هذا التأثير من شأنه أن يغير من الخواص الفيزيوحيوية والبيولوجية. Résumé : فرنسية أو انجلزية In order to contribute to the understanding of the impact of the parasitic relationship both parasitic and host plant, we have done this work aimed at studying the phytochemical and parasitic physiological relationship between the parasitic plant Cistanche violacea (Desf.) Beck and its hosts: Limoniastrum guyonianum Dur. and Haloxylon articulatum Bioss growing in the Oued Souf region. For this study, each parasite was collected in parallel with its host in tremes of space and time, collecting the H. articulatum plant during its vegetative growth phase and the parasitic plant during its fruitful development phase from the area of El-Khamcine (Reguba), while the L. guyonianum plant was collected during its floral stage and the parasitic plant during its fruitful growth phase from the Spitar-Deeb (Megran) region. After drying and crushing the samples, a series of physiochemical and phytochemical tests were corried out. In terms of physiochemistry, the acidity and electrical conductivity in the plant of C. violacea parasitized on L. guyonianum were assessed to be 5.63±0.03 and 7.05±0.05 mS/cm, respectively, while they were calculated to be 5.35±0.08 and 5.27±0.06 mS/cm in its parasitic on H. articulatum. In the four samples analyzed, the proportion of mineral and organic materials was inversely proportional. While we recorded the highest quantitative vqlues for carbohydrates and fats in the C. violacea parasitized on L. guyonianum plant 43.832±0.056 mg/g DM, 12.398±0.024 mg/g DM respectively. The C. violacea parasitized on H. articulatum plant also showed the best quantitive values for protein content (15.1±0.071 mg/g DM). In terms of phytochemistry, the results of the chemical screening the parasite plant now has a different host on flavonoids, tannins, anthocyanins, sterols, and triterpenes. Even without alkaloids and saponins, they remained in agreement. In addition to this, they prepared four different types of extract: crude, flavonoid phase ethyl acetate, tannins, and anthocyanin. We recorded the maximum yield of 16.183% at the crude extract of C. violacea parasitized on H. articulatum plant. When evaluating the quantitative content of each: Total polyphenols, flavonoids, tannins and anthocyanin from crude extracts, we recorded lower values in the C. violacea parasitized on L. guyonianum extract (19.055±0.197 mg E GA/g Ex, 5.769±0.353 mg E Q/g Ex, 0.121±0.002 mg E GA/g Ex and 0.167±0.047 mg E C-3-G/g Ex respectively). Regarding the qualitative estimation using HPLC, the results showed that the total number of phenolic compounds for both parasites converged, whereas a greater number was found in the hosts. Seven out of 57 reference compounds were found in the extract of the C. violacea parasitized on H. articulatum, and they were each: gallic acid, chlorogenic acid, vanilin, p-coumaric acid, rutin, naringin, and quercetin. While FTIR analysis of plant extracts revealed the presence of all hydroxylation functions (OH), methyl groups (CH), carbonyl groups (C=C/C=O), as well as the distinctive connections of aromatic rings (C-C). When it came to antioxydant activity, the flavonoidal extract from C. violacea parasitized on L. guyonianum produced higher DPPH• radical inhibition (IC50=0.011±0.002 mg/mL). While both parasites' tannin extracts had the highest levels of reducing power assay and total antioxidant capacity, we found that the valuable C. violacea parasitized on L. guyonianum extract had an EC50= 0.055±0.001 mg/mL and 488.493±0.060 g E As A/g Ex. The tannins extract for the parasitic C. violacea plant on L. guyonianum plant had the strongest UV protective factor, estimated at SPF = 27.434±0.020. According to statistical analysis, the parasite plant's physiochemical and phytochemical traits differ significantly from those of the host plant. The disparities between the entire quantitative content of oranic matter and the quantitative content of primary metabolites, as well as the differences between the quantitative content of polyphenols and their percentage, have amply illustrated these impacts. Along with the quantified variations in antioxidant activity amongst the several investigated extracts. In summary, it can be inferred from the data that the host plant's variation in the parasitic relationship has an impact on the metabiotic content of the parasite plant, and that this effect is directly reflected in the effectiveness of its effective products. Such a crucial interaction would alter host plants' physiological and biological characteristics as well as their ability to function biochemically.
أطروحة دكتوراه تخصص بيولوجيا وفيزيولوجيا النبات في العلوم الطبيعية و الحياة
Keywords: التطفل؛ الذنون Cistanche violacea (Desf.) Beck.؛ الزيتة Limoniastrum guyonianum Dur.؛ الباقل Haloxylon articulatum Bioss.؛ المعايير الفيزيوكيميائية؛ المعايير الفيتوكيميائية; Parasitism, Cistanche violacea (Desf.) Beck, Limoniastrum guyonianum Dur., Haloxylon articulatum Bioss., physiochemical parameters, phytochemical parameters.